The Public Servant and the Auteur: A Comparative Analysis of Julie Andem’s and Sam Levinson’s Showrunning Approaches - Marghitu, Stefania; Rustad, Gry (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2025)
This article compares the production/showrunner practices and representation of two of the most successful teen television series of the 2010s, Skam (NRK, 2015–2017) and Euphoria (HBO, 2019–). It compares the collaborative public service production practice under Julie Andem’s Skam with the perpetuation of the singular male auteur through Sam Levinson’s authorial control in HBO’s “prestige” teen series Euphoria. We argue that Andem’s and Levinson’s showrunning approaches create two very different representations of growing up. Andem’s mission allows us to view her as a civil servant for social media meets public service teen programming, whereas Levinson’s film background and personal struggles with addiction dominate popular Euphoria discourse. Andem incorporates intermediality as an ethnographic means to connect to youth audiences’ tangible issues through research and social media intimacies, whereas Levinson adapts a cinematic intertextual approach.